ANALISIS SEGITIGA KEBIJAKAN KESEHATAN DALAM PEMBENTUKAN UNDANG-UNDANG TENAGA KESEHATAN - Yuningsih, Rahmi (Jurnal Aspirasi, 2014)
In order toachieve the national health developments goals, we need health workforce who are competent, responsible, uphold ethical standards and spread evently all over Indonesia. But in fact, health workforce in Indonesia still face a lot of problem. Therefore the parliament and the government formed health workforce act as a legal reference to handle the problems. This research was conducted to determine health policy triangle in forming health workforce act. With qualitative approach, the study concluded that the actors come from the government, the president, the legislators, interest groups and political party. The content include aspects of professionalism and the relationship between the health workforce. The context includes aspects of cultural, social, political, economic, and legal. The process began in 2010 until 2014. This study recommended that in order to get common perspective, the public and the stakeholders should get involved more intensely.